Characterizations of food-derived ellagic acid-Undaria pinnatifida polysaccharides solid dispersion and its benefits on solubility, dispersity and biotransformation of ellagic acid. (1st July 2023) - Li, Zhao-Rong; Jia, Rui-Bo; Cai, Xueyuan; Luo, Donghui; Chen, Chong; Zhao, Mouming
Graphical abstract: Highlights: EA/UPP SDs significantly increased the EA solubility and dispersity. Crystalline transformation was one of the reasons for EA solubility enhancement. EA/UPP SDs were mostly maintained by hydrogen bonds and hydrophobic interactions. EA/UPP SDs significantly enhanced the EA biotransformation process. Abstract: The current study was aimed to enhance the solubility, dispersibility and biotransformation efficacy of ellagic acid (EA) by preparing food-derived ellagic acid- Undaria pinnatifida polysaccharides solid dispersion (EA/UPP SD). The results demonstrated that the solubility of EA/UPP SD was improved from 0.014 mg/mL to 0.383 mg/mL, and the enhancement was related to converting to a more amorphous state and restraining its self-aggregation during the mechanochemical process. The structure of EA/UPP SDs was mostly maintained by hydrogen bonds and hydrophobic interactions between EA and UPP. Moreover, the result of in vitro anaerobic incubations showed the biotransformation process was improved with EA/UPP SD addition to substrate due to the advance of microbial accessibility in EA dispersion. Altogether, these results indicated that the EA/UPP SDs expanded the application of EA by increasing the solubility and dispersity, and provided a theoretical basis for bioconversion efficiency enhancement.